New Prophet versus the State (A Study of the Phenomenon of New Religious Streams in Indonesia) - Zuly Qodir (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
This paper elaborates a phenomenon of the new Prophet in Indonesia. The New prophet of community is left (separated/heretic) by Majlis Ulama Indonesia (MUI) because such community is considered to perform heresy in religious mainstream (Islam). Why does this grow? What is simultaneous aspect within social ills, such as state failure in managing plurality in Indonesia, or is that connected with religious mission (Dakwah) in this contemporary phenomenon? This paper introduces state failure on dakwah/mission in Islam, pluralism management, and destructed national politics and economic growth. In this paper I describe mass destructive on sect (heresy) community by MUI. This paper presents religious sociological perspective as religion is looked as a social reality, not as religious dogma and state preposition. The New Prophet is at a diametrical position to the state (new prophet vis a vis state).Keywords: new prophet, heresy, state, MUI